Screening for antimicrobial activity of ten medicinal plants used in colombian folkloric medicine : A possible alternative in the treatment of non-nosocomial infections (2006)
ABSTRACT: Background: The antimicrobial activity and Minimal Inhibitory Concentration (MIC) of the extracts of Bidens pilosa L., Bixa orellana L., Cecropia peltata L., Cinchona officinalis L., Gliricidia sepium H.B. & K, Jacaranda mimosifolia D.Don, Justicia secunda Vahl., Piper pulchrum C.DC, P. paniculata L. and Spilanthes americana Hieron were evaluated against five bacteria (Staphylococcus aureus, Streptococcus β hemolític, Bacillus cereus, Pseudomonas aeruginosa, and Escherichia coli), and one yeast (Candida albicans). These plants are used in Colombian folk medicine to treat infections of microbial origin. Methods: Plants were collected by farmers and traditional healers. The ethanol, hexane and water extracts were obtained by standard methods. The antimicrobial activity was found by using a modified agar well diffusion method. All microorganisms were obtained from the American Type Culture Collection (ATCC). MIC was determined in the plant extracts that showed some efficacy against the tested microorganisms. Gentamycin sulfate (1.0 µg/ml), clindamycin (0.3 µg/ml) and nystatin (1.0 µg/ml) were used as positive controls. Results: The water extracts of Bidens pilosa L., Jacaranda mimosifolia D.Don, and Piper pulchrum C.DC showed a higher activity against Bacillus cereus and Escherichia coli than gentamycin sulfate. Similarly, the ethanol extracts of all species were active against Staphylococcus aureus except for Justicia secunda. Furthermore, Bixa orellana L, Justicia secunda Vahl. and Piper pulchrum C.DC presented the lowest MICs against Escherichia coli (0.8, 0.6 and 0.6 µg/ml, respectively) compared to gentamycin sulfate (0.9 8g/ml). Likewise, Justicia secunda and Piper pulchrum C.DC showed an analogous MIC against Candida albicans (0.5 and 0.6 µg/ml, respectively) compared to nystatin (0.6 µg/ml). Bixa orellana L, exhibited a better MIC against Bacillus cereus (0.2 µg/ml) than gentamycin sulfate (0.5 µg/ml). Conclusion: This in vitro study corroborated the antimicrobial activity of the selected plants used in folkloric medicine. All these plants were effective against three or more of the pathogenic microorganisms. However, they were ineffective against Streptococcus β hemolytic and Pseudomonas aeruginosa. Their medicinal use in infections associated with these two species is not recommended. This study also showed that Bixa orellana L, Justicia secunda Vahl. and Piper pulchrum C.DC could be potential sources of new antimicrobial agents.